(untitled) (Journal of Computational Mathematics, 2021)
This paper is concerned with the numerical solution of delay differential equations(DDEs). We focus on the error analysis of one-leg methods applied nonlinear stiff DDEs. It is proved that an A-stable one-leg method with a simple linear interpolation is D-convergent of order p, if it is consistent of order p in the classical sense.